(untitled) (Journal of the Bangladesh Agricultural University, 2013)
A study was conducted to identify how aquaculture assists in developing sustainable livelihood to the fish farming community in rural Bangladesh during the period from January to December, 2009. The Sustainable Livelihood Approach (SLA), a conceptual framework that aims to ameliorate poverty was applied to understanding the role of aquaculture in the Mymensingh area of the North-central Bangladesh. The study used the SLA as a foundation or main basis of analytical tool to identify the means and ways to enhance the livelihood of fish farmers. The analysis reveals how fish farmers can achieve positive sustainable livelihood through access to a wide range of livelihood assets. Higher economic return (BDT 1,19,360/ha/year) and social benefits were found to be gained by the fish farming community through human capital development. Lack of operating capital, vulnerability and insufficient institutional support were identified as major constraints to long term sustainability. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14933 J. Bangladesh Agril. Univ. 10(2): 391-402, 2012